Mössbauer spectroscopic study of the early crystallization stage of iron(III) hydroxide particles - Conforto, E.; Rechenberg, H. R.; Jafelicci, M. [UNESP] (Elsevier, 1986)
Mössbauer spectroscopy was used to investigate the early aging stage of iron(III) hydroxide sols prepared by oxidation of Fe(CO)5 in ethanolic solution, followed by vacuum drying at room temperature. One sample was composed of amorphous particles, while two other samples were partially crystallized, either as a result of solvent change or of spontaneous aging. The main results of Mössbauer measurements in the 80-320 K temperature range are: (a) partially crystallized particles exhibit a strong, S-shaped temperature dependence of the quadrupole splitting, in contrast to a weak and linear variation for amorphous particles; (b) the recoilless fraction temperature dependence is affected by vibration of the particles as a whole, with an effective force constant which is smaller for crystallized particles than for amorphous ones. Furthermore, the former exhibit anf-factor discontinuity near 0°C, which is attributed to melting of a surface layer built up during the crystallization process. © 1986.
Keywords: colloidal state; Iron hydroxide; microcrystals; Mössbauer spectroscopy; recoilless fraction; CHEMICAL REACTIONS - Oxidation; SPECTROSCOPY, MOSSBAUER - Applications; COLLOIDAL STATE; IRON(III) HYDROXIDE PARTICLES; RECOILLESS FRACTION; IRON COMPOUNDS